IDENTIFICATION OF THE MOLUCCAN MEGAPODE (Eulipoa wallacei) NATURAL HABITAT IN HARUKU ISLAND, INDONESIA AND ITS VEGETATION COMPOSITION - Leimena, Handy Erwin Pier; Sjarmidi, Achmad; Syamsudin, Tati Suryati (BIOTROPIA, 2023)
The characteristics of island vegetation greatly influence the activities of endemic birds in island areas, such as the Moluccan endemic megapodes (Eulipoa wallacei) on Haruku Island. Therefore, it is essential to identify the specific location of the habitat utilized by individual birds for their daily activities on Haruku Island and to analyze the composition of the vegetation and the variety of plant species. Identification of bird habitat locations using radio-tracking on four newly hatched chicks and four adult birds. A total of 330 individual tracking points were recorded during the study period. The vegetation sample used a total of 420 plots for seedlings, saplings, poles, and trees which were then analyzed for importance value index (IVI), diversity, evenness, and similarity. We found that the Tanjung Maleo forest was their nesting habitat, while the Marunimei and Lalean forests were their daily habitats. A total of 91 plant species and 60 plant families were discovered with the vegetation diversity value of the three habitats was moderate (H’mean = 3.07) and tended to be dominated by air plant (Kalanchoe pinnata), sword fern (Nephrolepsis exalta), cogongrass (Imperata cylindrica), coco-grass (Cyperus rotundus), Indian camphorweed (Pluchea indica), and lanzone (Lansium domesticum) (Emean = 0.88), and have a relatively low level of species similarity between habitats (SImean = 38.30%). We found that the daily habitat of the Moluccan megapode on Haruku Island was around their nesting sites and has a complex structure because it was composed four vegetation strata. Therefore, for conservation purposes, habitat management must prioritize preserving forest habitats around the bird nesting sites.